2021
DOI: 10.1177/0032258x211018787
|View full text |Cite
|
Sign up to set email alerts
|

The weaponising of COVID-19: Contamination prevention and the use of spit hoods in UK policing

Abstract: The COVID-19 pandemic has produced a radically changed world for everyone, but its effects on police officers has been particularly acute. Officers have been subject to increased cough and spit attacks as offenders have sought to weaponise the coronavirus, and forces have responded by encouraging officers to use enhanced methods of contamination prevention. The controversial argument of whether using ‘spit hoods’ is a necessary tool in policing has been resurrected, although evidence of their ineffectiveness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Though COVID weaponisation is not specific to the UK and has been reported in several other countries throughout the pandemic ( Ackerman and Peterson, 2020 ; De Camargo, 2021c ; Drew and Martin, 2020 ; Ong and Azman, 2020 ; Strote et al, 2021 ), this is the first study to scope the size of the issue and empirically examine the link between COVID weaponisation and the psychological wellbeing of police officers in England and Wales.…”
Section: Discussionmentioning
confidence: 97%
“…Though COVID weaponisation is not specific to the UK and has been reported in several other countries throughout the pandemic ( Ackerman and Peterson, 2020 ; De Camargo, 2021c ; Drew and Martin, 2020 ; Ong and Azman, 2020 ; Strote et al, 2021 ), this is the first study to scope the size of the issue and empirically examine the link between COVID weaponisation and the psychological wellbeing of police officers in England and Wales.…”
Section: Discussionmentioning
confidence: 97%
“…Although I will never know the reasons why the remaining eight officers did not respond, the original request asked for officers to discuss their fears and anxieties of policing the pandemic with little to no personal protective equipment (PPE), and to ruminate on managerial response. Originally officers voluntarily contacted me, and so it is very possible, judging by the divulgences and disclosures in the papers published by the author on these early interviews ( De Camargo 2021a , 2021b , 2021c ; De Camargo and Whiley 2021 ), that some officers used the opportunity to air grievances, complaining ‘in a safe space’ with promised anonymity ( Jeschke et al, 2021 ). I did not offer them any compensation for their time, and often researcher-researched relationships are based on some level of reciprocity.…”
Section: Methodsmentioning
confidence: 99%
“…Hine et al (2018) found that almost half (44%) of the officers involved in these events, events that included such things as being kicked, punched, head-butted, spat-on, bitten or a combination of any of these, reported sustaining an injury. Any number of these assaultive injuries may cause work-related anxiety, but critically since the COVID-19 pandemic, there is a very real concern of the risk of viral infections from SARS-CoV-2 (De Camargo, 2021). Not only are these opportunistic assaults, but they are also acts of insult which may further exacerbate the negative attitudes between civilians and police, increasing the potential for both physical and mental harm.…”
Section: Methodsmentioning
confidence: 99%